2023
DOI: 10.3389/fspor.2022.1089579
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-derived physical activity and sedentary behaviors in individuals with newly diagnosed type 2 diabetes: A cross-sectional study from the Danish nationwide DD2 cohort

Abstract: IntroductionHabitual physical activity behaviors of individuals with new-onset type 2 diabetes are largely unknown. We aimed to investigate accelerometer-derived physical activity behaviors in individuals with newly diagnosed type 2 diabetes. We also examined sociodemographic and health-related correlates of a high-risk physical activity profile.MethodsThis cross-sectional study used data from 768 participants enrolled in an intervention study nested within the Danish Centre for Strategic Research in Type 2 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The results of our study indicated that LST and current smoking were independently associated, regardless of the diabetes mellitus status. This result is consistent with those of a previous cross-sectional study in individuals with diabetes mellitus that reported current smoking as a risk factor for a high-risk physical activity profile, defined as high sedentary time (>648 min/day) combined with low moderate-to-vigorous physical activity (<30 min/day) [40]. Another study of the general population in the United States also found that sedentary behavior was higher in current smokers than in non-smokers and past smokers and that past smokers, compared with non-smokers, had higher sedentary behavior [41].…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study indicated that LST and current smoking were independently associated, regardless of the diabetes mellitus status. This result is consistent with those of a previous cross-sectional study in individuals with diabetes mellitus that reported current smoking as a risk factor for a high-risk physical activity profile, defined as high sedentary time (>648 min/day) combined with low moderate-to-vigorous physical activity (<30 min/day) [40]. Another study of the general population in the United States also found that sedentary behavior was higher in current smokers than in non-smokers and past smokers and that past smokers, compared with non-smokers, had higher sedentary behavior [41].…”
Section: Discussionsupporting
confidence: 92%
“…7 8 28 29 We identified few studies that used device-based measurements among individuals with diabetes or prediabetes to report physical activity intensities and adherence to WHO recommendations. A Danish study by Domazet et al 30 found that 62% of individuals with a median age of 61.8 years and newly diagnosed type 2 diabetes met the recommendations. A Swedish population-based study by Hult et al 31 found that 43% of 70-year-old adults with diabetes adhered to the WHO recommendations.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…other health behaviors like smoking, alcohol use, and diet quality. [10][11][12] PA has consistently been associated with different measures of perceived health, such as healthrelated quality of life (HRQOL), general health, and life satisfaction. [13][14][15] Research also supports MSA as a positive predictor of other health-related behaviors directly associated with health outcomes.…”
Section: Introductionmentioning
confidence: 99%